A perfect match? The dampening effect of interethnic marriage on armed conflict in Africa. (November 2022) - Demarest, Leila; Haer, Roos
How does interethnic marriage influence the occurrence of ethnic violence in sub-Saharan Africa? Previous studies on the relationship between intergroup contact and conflict onset have produced mixed findings. Some scholars have argued that this might be due to the way interethnic contact is measured. Building on insights of social psychology, this study examines the influence of interethnic marriage as the ultimate form of positive intergroup contact. In doing so, we combine information of the Demographic and Health Surveys with event data on ethnic conflict. Our analysis shows that areas with higher levels of exogamy significantly experience less ethnic conflict.